Numerical solution of a nonlinear singular Volterra integral system by the Newton product integration method - Babayar-Razlighi, B.; Soltanalizadeh, B. (Mathematical and computer modelling, 2013)
In this paper, we consider a nonlinear system of Volterra integral equations, and apply Newton’s method to linearize it. We solve each step of Newton’s system by the product integration technique. Also, we provide the sufficient conditions for convergence of the numerical method. Finally, we give a test problem to illustrate the applicability and accuracy of the presented method.